Implementasi KUR Syariah Berbasis Rahn Tasjily dalam Pengembangan UMKM di PT Pegadaian - Rizkyanti, Rizkyanti; Damirah; Nurfadhilah; Musmulyadi (LPPM STIEM BONGAYA, 2025)
This study aims to analyze the implementation of Sharia-based People’s Business Credit (KUR Syariah) using the Rahn Tasjilycontract in supporting Micro, Small, and Medium Enterprises (MSMEs) at PT Pegadaian CP Parepare. It focuses on the procedural compliance with Maqashid Shariah and its contribution to MSME growth. A qualitative case study was conducted through semi-structured interviews, observation, and documentation involving Pegadaian staff and financing recipients. Data were thematically analyzed and validated through source triangulation. Findings show that the KUR Syariah disbursement process is efficient, with simple requirements and fast procedures. The Rahn Tasjily contract complies with DSN-MUI Fatwa No. 68/DSN-MUI/III/2008 and upholds Maqashid Shariah by avoiding riba, gharar, and maysir, with a maintenance costs (mu’nah) of 0.14 % every month. This financing has positively impacted MSMEs by increasing turnover, production capacity, market reach, and employment. However, some issues remain, such as fund misallocation and limited mentoring. The study highlights the importance of inclusive, fair, and Sharia-compliant financing for sustainable MSME development. Its originality lies in the integration of normative and empirical analysis of Rahn Tasjily practices in a non-bank institution, based on real client experiences.